Sliding wear of CaZrO₃-MgO composites against ZrO₂ and steel - Silva, Abílio (2017)
The wear behaviour of a fine grained and dense CaZrO₃-MgO composite is presented. Un-lubricated Pin-on-disc tests at room temperature have been performed using 10 N as normal force and 0.10–0.15 ms⁻¹ as sliding rate and ZrO₂ and steel counterparts. The coefficient of friction versus the sliding distance and the specific wear, together with a complete microstructural analysis of the worn surfaces by field emission scanning electron microscopy is reported. The composite presents a wear resistance similar to other ceramics under ceramic/ceramic sliding contact and improved wear resistance in contact with steel. Initial wear is dominated by abrasion independently of the chemical nature of the counterpart. The second stage wear depends on the characteristics of the third body formed. Zirconia leads to a brittle particulate third body with little protective capability. Steel forms a strongly bonded and plastic cermet third body that protects the material limiting the level of further wear.